PENGARUH PEMBANGUNAN INDEKS MANUSIA (IPM) DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Fifi Rahayu; Mardiatul Husna; Nisfil Vitra; Muhammad Kevin; Fahri Berlianda; Andini Pratiwi; Jolianis Jolianis (STKIP Pesisir Selatan, 2026)
This study aims to analyze the influence of the Human Development Index (HDI) and investment on economic growth in Indonesia during the period 1990–2024. The study uses a quantitative approach with an associative research type and utilizes secondary data obtained from the Central Bureau of Statistics and the World Bank. The analytical method used is multiple linear regression, after first conducting a stationarity test for time series data. The results of the analysis indicate that neither HDI nor investment have a significant effect on Indonesia's economic growth, either partially or simultaneously. The HDI regression coefficient is negative (-0.014) with a probability of 0.97, while the investment regression coefficient is positive (4.17) with a probability of 0.34, both of which exceed the 10 percent significance level. The coefficient of determination (R-squared) value of 0.028 indicates that only 2.8% of the variation in economic growth can be explained by HDI and investment, while the remainder is influenced by other factors outside the research model. This finding strengthens previous research stating that HDI and investment are not always the main determinants of economic growth, so further studies are needed by considering other macroeconomic variables.